2011
DOI: 10.1038/bcj.2011.6
|View full text |Cite
|
Sign up to set email alerts
|

Highly skewed T-cell receptor V-beta chain repertoire in the bone marrow is associated with response to immunosuppressive drug therapy in children with very severe aplastic anemia

Abstract: One of the major obstacles of immunosuppressive therapy (IST) in children with severe aplastic anemia (SAA) comes from the often months-long unpredictability of bone-marrow (BM) recovery. In this prospective study in children with newly diagnosed very severe AA (n=10), who were enrolled in the therapy study SAA-BFM 94, we found a dramatically reduced diversity of both CD4+ and CD8+ BM cells, as scored by comprehensive V-beta chain T-cell receptor (TCR) analysis. Strongly skewed TCR V-beta pattern was highly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…Healthy adult controls demonstrated high complexity scores with low standard deviation (127±8). As described earlier, 20 bone marrow from healthy children had a high CS SPECTRATYPING similar to adult controls.…”
Section: Skewing Of Complementarity Determining Region 3 Length Polymsupporting
confidence: 68%
See 1 more Smart Citation
“…Healthy adult controls demonstrated high complexity scores with low standard deviation (127±8). As described earlier, 20 bone marrow from healthy children had a high CS SPECTRATYPING similar to adult controls.…”
Section: Skewing Of Complementarity Determining Region 3 Length Polymsupporting
confidence: 68%
“…This finding corresponds well to our earlier observations. 20 Based on CSSPEC-TRATYPING, a distinction between diseased cohorts was not possible because of the associated high standard deviations. Healthy adult controls demonstrated high complexity scores with low standard deviation (127±8).…”
Section: Skewing Of Complementarity Determining Region 3 Length Polymmentioning
confidence: 99%
“…A correlation between the frequency of the clonotypes and haematological response to IST supports the disease specificity of these clonotypes, indicating that they may be used as markers to assess disease activity, treatment response and relapse [22,23]. It has been reported that in addition to the decline in the frequency of the immunodominant clones, restoration of TCR variability can be observed in aAA patients who respond to IST [12,24]. At the time of disease relapse, the original, putatively pathogenetic dominant clones reappear and are sometimes accompanied by Table 1.…”
Section: Cd8 1 T Cellsmentioning
confidence: 76%
“…12 A Gaussian CDR3 length distribution pattern was observed for both TRA and TRB reads, suggesting the diverse and well-distributed TCR repertoire populations in healthy donor ID 001 (Fig. 1d).…”
Section: Establishment Of Tcr Sequencing Platform By Ion Torrent Pgmmentioning
confidence: 89%